Peningkatan Kemampuan Motorik Halus Anak Kelompok A Melalui Kegiatan Bermain Papercraft (Penelitian Tindakan di Kelompok A TK Alam Rizkia, Cimpaeun-Tapos, Depok, 2017) - Nurjannah, Dwi (STIT Al-Marhalah Al-Ulya Bekasi, 2018)
Abstract: The background of this study is the low motor skills of early childhood in group A in the Natural Kindergarten Rizkia. This can be seen from the weakness of fine motor in moving the fingers of the hands, coordinate the eyes and hands, and the accuracy of flexibility of the child's fingers. The purpose of this study is to improve fine motor skills through papercraft play activities. The method used in this research is classroom action research method using Kemmis and Taggart cycle model through four stages namely planning, implementation, observation, and reflection which is done by two cycles. The subjects of the study were 16 students of class A. Data collection is done by observation, documentation, and interview. The results of the study conducted during two cycles observed the development of fine motor skills of group A children experienced an increase in each cycle. Pre-action (pre cycling) was 34%, in cycle I was 60.6% with 26.6% increase and in second cycle was 83.82% with an increase of 23.22%. Thus the percentage improvement of fine motor ability of group A children through papercraft activity has achieved success indicator that is more than 75%. This means that papercraft play activities are very effective and can be used in improving the fine motor skills of children group A.